Pemanfaatan Canva Sebagai Media Inovatif Dalam Pengembangan Bisnis Digital UMKM - Jecky Danvelty Rumaropen; Dion Tumbelaka; Alea Karwur; Florensita G. Singkoh; Irma Tarontong; Grace Christien Sumakul (Jurnal Ekonomi dan Bisnis Digital, 2025)
Digital transformation has become an essential need for Micro, Small, and Medium Enterprises (MSMEs) to stay competitive in an increasingly dynamic market. One innovative solution widely adopted is Canva, a web-based graphic design platform that enables users to create various promotional materials and instant websites without technical expertise. This study aims to examine the use of Canva as a digitalization support tool for MSMEs, particularly in branding, marketing, and rapid website development. The methods used include literature review and observation of Canva’s practical use among MSME actors. The findings show that Canva simplifies the design process, increases time and cost efficiency, and strengthens brand identity. However, limitations in the free version and design customization present certain challenges. Overall, Canva proves to be an effective, practical, and affordable strategic solution in accelerating MSME digitalization in Indonesia.